Family history of hypertension increases risk of preeclampsia in pregnant women: a case-control study - Endeshaw, Mulualem; Abebe, Fantu; Bedimo, Melkamu; Asrat, Anemaw; Gebeyehu, Abebaw; Keno, Alemayehu (Faculty of Medicine, Trisakti University, 2016)
Background Preeclampsia is one of the leading causes of maternal and fetal morbidity and mortalities worldwide. Despite extensive research, the underlying cause of preeclampsia remains poorly understood. This study aimed to offer compelling evidence on the important risk factors of preeclampsia in Amhara region, Ethiopia.MethodsA case control study was conducted in public health facilities of Bahir Dar city from September 2014 to January 2015. A total of 453 (151 cases and 302 controls) pregnant women were enrolled in this study. Hemoglobin level and urinary tract infection (UTI) status were collected from clinical notes. Oral examination was performed by a dentist for detection of periodontal diseases. Univariate and multiple logistic regression analysis was conducted to determine the relationship of all the independent variables with the outcome variable. A p-value <0.05 was declared statistically significant.ResultAdvanced maternal age (AOR=4.79;95% CI 1.031-22.18), family history of hypertension (AOR=11.16;95% CI 5.41-41.43), history of diabetes mellitus (AOR=6.17;95% CI 2.11-20.33), UTI in the current pregnancy (AOR=6.58;95% CI 2.93-14.73), failure to comply with iron and folic acid supplement during pregnancy (AOR=8.32;95% CI 3.35-20.62), lack of exercise (AOR=3.33;95% CI 1.35-8.17), multiple pregnancy (AOR=4.05;95% CI 1.57-12.27), anemia (AOR=4.19;95% CI 1.27-13.92), and periodontal disease or gingivitis (AOR =3.51;95% CI 1.14-10.83) were associated with preeclampsia.Conclusion Family history of hypertension was the most dominant risk factor for preeclampsia in pregnant women. Encouraging pregnant women to have health seeking behavior during pregnancy would provide a chance to diagnose preeclampsia as early as possible.